(untitled) (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Fatigue is a common and debilitating symptom among patients with chronic kidney disease (CKD) receiving maintenance hemodialysis. It negatively affects physical functioning, psychological well-being, treatment adherence, and quality of life. Despite its high prevalence, fatigue is often under-recognized in routine clinical practice, highlighting the need for systematic assessment and identification of contributing factors. Objectives: To determine the prevalence and severity of fatigue among patients undergoing maintenance hemodialysis for CKD and to evaluate its association with demographic characteristics, clinical variables, and laboratory parameters. Methods: A hospital-based cross-sectional observational study was conducted among adult CKD patients receiving maintenance hemodialysis for at least three months at a tertiary care hospital in Erode, Tamil Nadu. Fatigue was assessed using the Fatigue Severity Scale (FSS). Demographic, clinical, dialysis-related, and laboratory data were collected using a structured case record form and analyzed using descriptive and inferential statistics. Results: Fatigue was highly prevalent among maintenance hemodialysis patients, with varying degrees of severity. Significant associations were observed between fatigue severity and selected demographic, clinical, dialysis-related, and laboratory variables. Conclusion: Fatigue is a significant symptom among patients receiving maintenance hemodialysis. Routine assessment and multidisciplinary interventions targeting modifiable factors may improve symptom management, functional status, and quality of life